Pengaruh Kebijakan Perusahaan dan Human Capital Terhadap Nilai Perusahaan dengan Kinerja Perusahaan Sebagai Variabel Intervening (Studi Empiris Pada Perusahaan Consumer Periode 2010-2012) - Asror, Muhammad Habib, Dr. Triyono, M.Si (2016)
This study aimed to test whether the company's performance mediated the company policy and human itelectual capital in influencing the value of the firm. The aim of this research is (a) the analyze influence of company's policy that proxy with capital expenditure, leverage, human intelectual capital to company's performance, (b) the analyze influence of company's policy that proxy with capital expenditure, leverage, human intelectual capital to firm value, (c) the analyze influence of company's performance to firm value, (d) the analyze influence effect company's performance into relationships between company's policy with frim value. The study took a sample of 30 consumer companies listed in Indonesia Stock Exchange period of 2010 until 2012, with purposive sampling method. Results of this research show that Capital expenditure is not significant negative effect on the company's performance but have a positive effect on firm value financial leverage significant positive effect on company's performance, but have negative effect firm value. While the human intelctual capital has a negative effect on company's performance, but no positive effect on firm value. Specific findings of this research is that the company's performancenot don't have mediates the influence of human intelctual capital and firm value. Keywords: Capital expenditure, leverage, human intelctual capital firm performance, and firm value